QUALITATIVE CHARACTERISTICS OF TRUNK PHYTOMASS AND CROWN COMPONENTS OF FOREST FORMING SPECIES OF NATIONAL NATURAL PARK “PRYPIAT-STOKHID” - Lakyda, P. I.; Melnyk, О. М. (Forestry and Forest Melioration, 2018)
Introduction Research of biotic productivity of forests on the territory of our country has begun not so long time ago and some of regions and objects (especially objects of natural reserve funds) have no informational support for getting data about oxygen release and carbon sequestration functions in different components of planted forests. Aim of the research is to conduct biometric processing of research data, received after establishing temporary testing areas (TTA) for further evaluation of biotic productivity and ecological potential of “Prypiat-Stokhid” TTA forests. Research methodology and materials The TTA established by the authors (9 pcs) served as research data for informational support of evaluation of biotic productivity of “Prypiat-Stokhid” TTA forests. Through the research, the methodology of the prof. P. I. Lakyda was used; the aforementioned is oriented for developing of system of standards for phytomass of trees and stands components evaluation using the applied software. Research findings Wood density (р), as defined by О. І. Poluboiarynov – is physical quantity, which reflects the natural wood mass in volume unit. It is directly proportional to mass (m) and in inverse proportion to volume (v) of wood samples. Wood density in bark of common pine is within 390 to 470 kg? (sm3)-1, when the density of bark is from 207 to 287 kg? (sm3)-1. Wood density in bark of alder and birch in average is higher than in pine and are 488 and 520 kg? (sm3)-1 correspondingly. During the period from 15 to 47 years, increase of the density of all components of phytomass is observed. It should be mentioned that density of bark increases gradually during above period, when density of wood increases in two stages: extensively to 25 years and intensively from 25 to 47 years. Density of crown phytomass components changes with age in every tree species. The highest density of branches wood is observed in pine trees in age of 25 years, it is 584 kg? (sm3)-1, and the lowest one is in pine trees of 91 years old – 432 kg? (sm3)-1. An average value of leaves part (needles) in tree foliage is for pine – 63.4 %, alder and birch have 62.8 and 64.1%, correspondingly. Conclusions Natural and base wood density – main index of high-quality evaluation of tree crown branches and trunk phytomass components; Density of wood and bark of trunk of common pine, common alder and silver birch changes not only along the tree trunk, but also depends on taxation features, age first of all; Leaves part in tree foliage does not depend on age, diameter and height of the trunk and in average is: for pine – 63.4 %, alder 62.8 % and birch 64.1 %; An average solid content in 1 g of fresh leaves for pine is 0.435, for alder – 0.382 and for birch – 0.424.